The Development of Problem-based Learning Worksheet for the Material of Optical Instrument - Khotimah, Khusnul (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2024)
Student learner-centered creates interaction and activeness of teaching and learning activities in the classroom. Students can play an active role in learning by using Problem-Based Learning (PBL) based student worksheets. This study aims to 1) Know the results of the development of student worksheets Problem-Based Learning (PBL) on optical instrument material, 2) Know the quality/feasibility of student worksheets Problem-Based Learning (PBL) on optical instrument material, 3) Know the response of students to student worksheets Problem-Based Learning (PBL) on optical equipment material. This research is a Research & Development using 4D development procedures by Thiagarajan. The development phase includes define, design, develop, and disseminate, but this research is limited to the develop stage by conducting limited and field tests. The product developed is a student worksheet based on Problem Based Learning (PBL) on optical instruments for high school students. The quality of student worksheets based on Problem-Based Learning (PBL) on optical instrument material for Senior High School class XI which was developed based on the assessment of material experts, media experts and physics teachers obtained Very Good (VG) criteria. The response of students to student worksheet in limited trials and field trials obtained Very Good (VG) criteria. These results show that student worksheets based on Problem-Based Learning (PBL) can be used as teaching material in the learning process on optical instrument materials.